HASAN LANGGULUNG PARADIGM ABOUT APPRECIATION OF ISLAMIC VALUES IN EDUCATION - Mashur Al Mutahar; Muh. Nur Rochim Maksum; Defi Firmansah (Green Publisher, 2022)
Islamic values ??are something that is valuable for the effort that has been given, which has advantages and can be compared with something else. Islamic values ??as a driving force that is inherent in a person's soul so that it becomes a way of life. The pattern of human behavior must follow Islamic values ??accompanied by appreciation in the human being so that certain thoughts, attitudes, and feelings will develop. This study aims to examine more deeply Hasan Langgulung's paradigm of appreciation of Islamic values ??in education. This research uses library research method with descriptive, conceptual, and psychological approaches. The results of this study indicate: appreciation of Islamic values ??is a type of human learning process in life, by following the law in the learning process without violating existing rules. The appreciation of Islamic values ??in oneself is accompanied by a learning process in the presence of a stimulus from humans to practice Islamic values ??in education and various certain values ??so that these actions will be rewarded from human practice. If Islamic values ??have become human guidelines, if the human does not live it in the form of practice, then the human will feel uncomfortable in his life.